Aproximaciones teórico-conceptuales a la comprensión de las lógicas de empobrecimiento y segregación socio espacial (2018)
ABSTRACT: The purpose of this article is to provide a theoretical and methodological basis for the study and understanding of the processes of impoverishment and socio-spatial segregation that occur in our societies in contemporary contexts, where capitalist development and market economy have been determinant in the structuring of social inequalities and inequalities, exacerbating the gaps between wealth and poverty. Some references allow to locate the analysis of the phenomenon in Latin American and Colombian context oriented to understand, measure and generate public policies for the eradication of Poverty. What is also questioned is the place of the economic model in the processes of impoverishment and the perceptions that the population has about poverty and the institutional actions designed to combat it.